Programma: 19 juli: Paradise Now op Sarchinger Open Air, Regensburg; 14-15 augustus: Paradise Now op Ringfest, Köln (1997)
Programma: 19 juli: Paradise Now op Sarchinger Open Air, Regensburg; 14-15 augustus: Paradise Now op Ringfest, Köln.